Territorial Basis Associates: the Public Consortia’s Alternative in Brazil - Filippim, Eliane Salete; Abrucio, Fernando Luiz (Revista del CLAD Reforma y Democracia, 2016)
This document examines an associative strategy for the common problems solving to some territories, adopted in Brazil since the advent of the Law N° 11.107 of April 6th, 2005, which stimulated and regulated the consolidation of public consortia. From this Law, the municipalities found more legal security to associate with their partners or with other units of the Brazilian federation (states and Union), in order to implement public policies. The general aim of the study was to investigate the formation and the institutionalization of public consortia as a strategy to the territorial basis associates. In the methodological procedures, it was used the qualitative approach, once this work focused on observing the public consortia’s genesis, development and relationship networks, seeking to understand this phenomenon considering aspects that keep some subjectivity degree. It is about descriptive and interpretative research with the use of the strategy of the study of two cases of inter-municipal public consortium, whose characteristics provide reflection about the cooperation of the local territory scope. As conclusions of the study of these cases, some aspects are recommended to other ways of territorial cooperation and to new studies.
Keywords: Local Association; Cooperation; Municipalities; Brazil